NeuroFusion: A Unified Framework for Generalized Visual Stimulus Decoding from fMRI Across Datasets and Subjects - Muhammad Kashif; Matteo Ferrante; Nicola Toschi (Neuroinformatics, 2026)
Recent advancements in neural decoding have shown promising results in reconstructing visual experiences from brain activity. However, existing approaches focus primarily on decoding within a single dataset or subject, which limits generalization across various sources of neuroimaging. In this work, we propose a novel framework for the decoding of visual stimuli between subjects and between data sets, integrating neural recordings from multiple publicly available fMRI datasets. To address inherent intersubject and interdataset variability, we introduce a contrastive learning-based alignment strategy using image embeddings from a pre-trained IP-Adapter model. Our approach learns a shared latent space by aligning subject-specific neural representations with image features, enabling generalized decoding across both subjects and datasets. In addition, we propose a simple yet effective data augmentation method using ridge regression. This method synthesizes realistic fMRI-like signals from novel images by predicting voxel activity and injecting learned noise distributions, thus enhancing training diversity and model robustness. To the best of our knowledge, while several recent studies have explored cross-subject decoding, we extend recent cross-subject decoding efforts by training a single unified framework jointly across multiple public fMRI datasets and subjects, enabling cross-dataset transfer in addition to cross-subject generalization. We distinguish this multi-dataset unified training setting, where each dataset contributes training data, from a stricter leave-one-dataset-out transfer setting in which the target dataset is excluded from source pretraining and used only for lightweight alignment-layer adaptation. Empirically, our unified model achieves strong semantic reconstruction across datasets (e.g., up to 94.8% CLIP similarity on NSD (AUG) and 0.403 SSIM on BOLD5000 after lightweight finetuning), demonstrating robust cross-subject and cross-dataset transfer.

Deep Representational Similarity Learning for Analyzing Neural Signatures in Task-based fMRI Dataset - Muhammad Yousefnezhad; Jeffrey Sawalha; Alessandro Selvitella; Daoqiang Zhang (Neuroinformatics, 2021)

3D-Deep Learning Based Automatic Diagnosis of Alzheimer’s Disease with Joint MMSE Prediction Using Resting-State fMRI - Nguyen Thanh Duc; Seungjun Ryu; Muhammad Naveed Iqbal Qureshi; Min Choi; Kun Ho Lee; Boreom Lee (Neuroinformatics, 2020)

Multi-Objective Cognitive Model: a Supervised Approach for Multi-subject fMRI Analysis - Muhammad Yousefnezhad; Daoqiang Zhang (Neuroinformatics, 2019)

Temporal Information of Directed Causal Connectivity in Multi-Trial ERP Data using Partial Granger Causality - Vahab Youssofzadeh; Girijesh Prasad; Muhammad Naeem; KongFatt Wong-Lin (Neuroinformatics, 2016)